1989
DOI: 10.1111/j.1365-3083.1989.tb01198.x
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Non‐Specific Immunosuppression in Mice by Mycobacterial Infections and Its Relationship to Macrophage Activation

Abstract: The development of non-specific immunosuppression during the infection of different strains of mice with three mycobacterial species was evaluated by studying the immune response to a heterologous antigen (sheep red blood cells) and comparing it with the induction of non-specific resistance to a Listeria monocytogenes challenge. It was shown that early (at 15 days) immunosuppression developed in Mycobacterium avium-susceptible mouse strains infected with a high inoculum dose [2.5 x 10(8) colony forming units (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

1992
1992
2002
2002

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…avium infection in two additional murine strains: C57B1/ 6-lpr/lpr mice that are both autoimmunity-prone and Myco. avium-susceptible animals [8], and also C.D2 mice that are both non-autoimmune and Myco. avium-resistant animals [9].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…avium infection in two additional murine strains: C57B1/ 6-lpr/lpr mice that are both autoimmunity-prone and Myco. avium-susceptible animals [8], and also C.D2 mice that are both non-autoimmune and Myco. avium-resistant animals [9].…”
Section: Resultsmentioning
confidence: 99%
“…Previous investigations had also demonstrated that NZW and C57BI/6-lpr/lpr mice are susceptible (they carry the Bcgf allele of the Bcg gene) to Myco. avium infection, whereas NZB and C.D2 mice are resistant (bearing the Bcgr allele) to the same infectious agent [7][8][9][10].…”
Section: Micementioning
confidence: 99%
“…It has been reported in the literature that Mycobacteria antigens [15,34,35], and specifically ML antigens [5], inhibit superoxide production by macrophages. Our data clearly confirm these observations considering that ML or LE deeply suppressed O 2 -production by BMD macrophages.…”
Section: Macrophage Deactivation Induced By Mycobacterium Leprae Lipimentioning
confidence: 99%
“…The role of macrophages on the control of mycobacteria infection is still unclear despite the great efforts addressed to this issue [1,[3][4][5][6][7][8][9][10][15][16][17][18][19][20][21][22][23]. Since macrophages are the obligatory homing for pathogen mycobacteria in the tissues, we decided to investigate further the effects of dead M. leprae and its lipidic content on macrophage activation evaluating the phagocytic ability, superoxide production and tumour cell killing ability of these cells.…”
Section: Introductionmentioning
confidence: 99%
“…Measurement of the production of IFN-␥ from in vitro-cultured lung cells as described above for spleens was ruled out, because they produced inordinately low titers of IFN-␥ (data not shown). Because cells recovered from the lung comprised over 70% macrophages and other large cells, it is likely that this was due to either a relative shortage of T cells in cultures or suppression by products of activated macrophages (1,13). Lungs were removed from groups of three mice at different stages of infection and subjected to enzymatic digestion to generate single-cell suspensions (14).…”
mentioning
confidence: 99%